2019
DOI: 10.1002/celc.201901554
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Effective Electric Loads in Blended Insertion Electrodes for Lithium‐Ion Batteries

Abstract: Blending different types of active materials in one electrode is a great opportunity to improve the overall performance of lithium‐ion batteries. Despite considerable progress in the recent years, basic interactions, such as the specific impact of a single component on the blends’ properties, are not satisfactorily understood at the moment. In this study, the electric loads of the individual components of a blend are investigated using a special experimental setup in combination with model‐like blended electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 35 publications
(41 reference statements)
1
27
0
Order By: Relevance
“…Mixing three components at even ratio (33% for each), the ternary blend electrode presents highest electronic conductivity when all the other electrode parameters are controlled at same level (as list in Table 1) [45]. Redox activities studies reveal that each components in blend cathode can work independently and contributes to reduce the over-potential [46]. This is consistent with other reports.…”
Section: Ternary Blend Cathodessupporting
confidence: 86%
“…Mixing three components at even ratio (33% for each), the ternary blend electrode presents highest electronic conductivity when all the other electrode parameters are controlled at same level (as list in Table 1) [45]. Redox activities studies reveal that each components in blend cathode can work independently and contributes to reduce the over-potential [46]. This is consistent with other reports.…”
Section: Ternary Blend Cathodessupporting
confidence: 86%
“…applied during charge and discharge are inhomogenously distributed among the different electroactive materials. [14] Supported by simulation studies, the different working potentials result in significantly higher stress of one material at a given potential and the performance of the blend is negatively affected. [15] In contrast to these studies, blend electrodes are generally reported to show advantageous electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Liebmann et al. used a model system without intermixed particles to show that the currents applied during charge and discharge are inhomogenously distributed among the different electroactive materials [14] . Supported by simulation studies, the different working potentials result in significantly higher stress of one material at a given potential and the performance of the blend is negatively affected [15] .…”
Section: Introductionmentioning
confidence: 99%
“…After the fast charge/discharge for 50 cycles and the current density is restored to 200 mA g −1 , the capacity for the Fe 3 O 4 /CNTs@C composite rise to 776 mA h g −1 . It is notable that the capacity increases after 50 cycles, demonstrating that a thin and stable SEI film formed on the surface of active material improve its activity [13] . On the contrary, the Fe 3 O 4 @C sample cannot recover its capacity to the initial ones when the current density down to 0.2 A g −1 after a 50‐cycle test at 5 A g −1 , which may be due to destruction of the composite without CNTs reinforcing bands.…”
Section: Resultsmentioning
confidence: 99%
“…In recent decades, many of categories materials, such as oxides and sulfides as well as selenides of metal, have been extensively investigated and explored as anode materials for LIBs [9–15] . Among these materials, Fe 3 O 4 is considered as a favorable candidate material for LIBs owe to its relatively high theoretical capacity of 926 mA h g −1 [16] .…”
Section: Introductionmentioning
confidence: 99%